2022
DOI: 10.1111/padm.12909
|View full text |Cite
|
Sign up to set email alerts
|

Aggressions and associations: How workplace violence affects what public employees think of citizens

Abstract: Scholars have recently spent growing attention to what public employees think of citizens, which influences policy implementation through more manifest attitudes and behaviors. The origins of employees' positive and negative associations with citizens have, however, not been examined thus far. This study draws attention to workplace aggression as critical incidents in state‐citizen encounters and examines the traces they leave in employees' subsequent thinking about citizens. Building on social cognition and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(137 reference statements)
0
0
0
Order By: Relevance
“…Workplace aggression in healthcare is an immerging growing phenomenon as if the pandemic kindled an outrage against healthcare professionals. Previous research argued that being exposed to workplace aggression undoubtedly evokes emotional responses like anger, despair, or fear and the more harm-causing incidents of workplace aggression have a higher impact on female employees [123]. A review identified several staff-related causes of workplace aggression in healthcare: notably emotional dysregulation, distressing working conditions, unsupportive supervisors, inappropriate management, lack of instructions for handling aggressive incidents, and alcohol abuse [124].…”
Section: Workplace Aggression and Interrelated Variablesmentioning
confidence: 99%
“…Workplace aggression in healthcare is an immerging growing phenomenon as if the pandemic kindled an outrage against healthcare professionals. Previous research argued that being exposed to workplace aggression undoubtedly evokes emotional responses like anger, despair, or fear and the more harm-causing incidents of workplace aggression have a higher impact on female employees [123]. A review identified several staff-related causes of workplace aggression in healthcare: notably emotional dysregulation, distressing working conditions, unsupportive supervisors, inappropriate management, lack of instructions for handling aggressive incidents, and alcohol abuse [124].…”
Section: Workplace Aggression and Interrelated Variablesmentioning
confidence: 99%